DEVELOPMENT AND QUALITY EVALUATION OF MEAT FLOSS FROM BEEF, CHEVON AND PORK (2013)
Meat Floss (MF) is a meat product traditionally produced from beef. The MF is a shredded meat product that is light, easy to pack and nutrient retaining. However, information on yield and nutritional quality of MF has not been well documented. Therefore, MF from beef (MFB), chevon (MFC) and pork (MFP) were developed and evaluated for yield and quality. The raw beef, chevon and pork were obtained from thigh muscle and analysed for Dry Matter (DM) and Crude Protein (CP). The samples were cooked, shredded, fried for production of MF (MFB, MFC and MFP) and analysed for Product Yield (PY), DM and CP using standard procedures. Eating Qualities (EQ): aroma, flavour, tenderness, juiciness and texture were determined using a 9-point hedonic scale. Shelf stability of MF when differently packaged in acrylic bottle, polyethylene and polyamide for 21 days were assessed by measuring levels of Thiobarbituric Acid Reactive Substances (TBARS) using standard procedure. Based on EQ for MFB, Semi tendinosus (St), Semi membranosus (Sm) and Bicep femoris (Bf) obtained from raw beef were used to produce MF from St (MFSt), Sm (MFSm) and Bf (MFBf) using soya oil and their PY, CP and EQ were assessed. The TBARS levels of MFSt, MFSm and MFBf stored for 21 days in polyethylene were assessed. The most acceptable was used to produce MF using groundnut oil (GNO), soya oil (SOY) and palm oil (PMO) as frying media. The TBARS levels and Microbial Load (ML) of MF using GNO (MFGNO), SOY (MFSOY) and PMO (MFPMO) stored in three packaging media for three weeks were assessed. Data were analysed using descriptive analysis and ANOVA at p=0.05. The DM (%) of raw beef, chevon and pork were 28.0, 33.3, 35.8 and their CP (%) were 22.9, 21.2 and 22.7 respectively. The PY (g/100g) of MFB (70.1) and MFC (74.1) were higher than MFP (68.9). The CP (%) of the products were 39.8, 46.7 and 41.8 for MFB, MFC and MFP respectively. The EQ for MFB (7.4) was higher than MFC (6.6) and MFP (6.2). The TBARS (mg/100g) levels were MFB (2.4), MFC (2.8), and MFP (2.0). The PY (g/100g) were 53.9, 63.9 and 64.1 and CP (%) were 40.1, 36.6 and 37.9 for MFSt, MFSm and MFBf respectively. The EQ was significantly higher in MFSt than both MFSm and MFBf. The TBARS (mg/100g) levels were 1.8 (MFSt), 0.7 (MFSm) and 1.5 (MFBf). There were no significant differences in PY, CP and juiciness of MF from the three oil types. Though all the products were rated same in overall acceptability, MFPMO was most tender (6.4) and MFSOY was best in flavour (5.9). The TBARS (1.5 mg/100g) and ML (1.3 log10-2cfu/g/cm2) of MFSOY were highest irrespective of packaging media while TBARS (1.3) and ML (1.1) of polyethylene were low irrespective of the product. Meat floss contained about twice the protein in their respective raw meat and can be produced using any of groundnut oil, soya oil and palm oil. The products can best be kept in polyethylene.